2020
DOI: 10.1161/hypertensionaha.119.14309
|View full text |Cite
|
Sign up to set email alerts
|

Orthostatic Hypotension, Cardiovascular Outcomes, and Adverse Events

Abstract: Orthostatic hypotension (OH) is frequently observed with hypertension treatment, but its contribution to adverse outcomes is unknown. The SPRINT (Systolic Blood Pressure Intervention Trial) was a randomized trial of adults, age ≥50 years at high risk for cardiovascular disease with a seated systolic blood pressure (BP) of 130 to 180 mm Hg and a standing systolic BP ≥110 mm Hg. Participants were randomized to a systolic BP treatment goal of either <120 or <140 mm Hg. OH was defined as a drop in systolic B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 43 publications
2
54
1
4
Order By: Relevance
“…Em ECR, o controle da HA mostrou a diminuição de eventos CV sem aumento do no risco de HO ou quedas com lesão. [854][855][856] A HA mal controlada e determinados antihipertensivos, como os alfabloqueadores, podem provocar ou piorar a HO. A melhor opção para seu controle é o uso de medidas não medicamentosas como hidratação adequada, dieta normossódica, mudança lenta de decúbito, elevação da cabeceira e uso de meias elásticas.…”
Section: Hipotensão Ortostática E Pós-prandialunclassified
“…Em ECR, o controle da HA mostrou a diminuição de eventos CV sem aumento do no risco de HO ou quedas com lesão. [854][855][856] A HA mal controlada e determinados antihipertensivos, como os alfabloqueadores, podem provocar ou piorar a HO. A melhor opção para seu controle é o uso de medidas não medicamentosas como hidratação adequada, dieta normossódica, mudança lenta de decúbito, elevação da cabeceira e uso de meias elásticas.…”
Section: Hipotensão Ortostática E Pós-prandialunclassified
“…Orthostatic hypotension was not found to be related to higher risk for cardiovascular events. Although associated with hypotension-related hospitalizations and bradycardia, this risk was similar in the different arms of the study 21 . Finally, hemodynamic effects rather than tubular dysfunction are the proposed etiology for AKI cases 22 .…”
Section: Hypertension Definition and Treating Targets: Shifting To Lomentioning
confidence: 68%
“…16,22,23 Patients with orthostatic hypotension have been shown to be at increased risk for falls, ischemic stroke, coronary artery disease, heart failure, atrial fibrillation, CKD, cognitive function decline, and all-cause mortality, though a recent analysis from the systolic blood pressure intervention trial (SPRINT) study showed that orthostatic hypotension was not associated with a higher risk of cardiovascular disease events. [3][4][5][6][7][8][9][10]12,24,25 Less is known about orthostatic hypotension in patients with CKD. In the Irish Longitudinal Study on Ageing, 11% of participants with a GFR <60 ml/min/1.73m2 had orthostatic hypotension 14 .…”
Section: Discussionmentioning
confidence: 99%